The Impact of Distinctive Features of Blockchain Technology on the Customer's Agility: The Modified Role of the Requirements for the Implementation of Blockchain Technology-Applied Study in the Egyptian Pharmaceutical Companies - El-Abbasy , Einas Mohamed Mohamed (Jordan Journal of Business Administration, 2023)
This study aims to investigate to what extent the sample recognizes the distinctive features of blockchain technology, the requirements of the implementation of this technology and customer agility (sensing and responsing), as well as how this effect varies with the presence of a modifying variable (the requirements of the implementation of this technology), as the study aims to identify the significant differences between the views of the sample on the distinctive features of blockchain technology, the requirements of the implementation of this technology and customer agility according to the nature of the ownership of the company (foreign or private). The study was applied to 388 managers (top and IT managers of foreign and private pharmaceutical companies). Using SEM available in SmartPLS 2.0.M3, the study found that top and IT managers of foreign and private pharmaceutical companies recognize the presence of the distinctive features of blockchain technology, the requirements for its implementation and customer agility, as the results proved a positive significant effect of the distinctive features of blockchain technology on customer agility and a positive significant effect of the requirements of the implementation of blockchains on the relationship between them as a modifying variable. The study proved that there are statistically significant differences between the sample of mangers about distinctive features of blockchain technology and the requirements of the implementation of this technology in favor of foreign companies, while there have been no significant differences in relation to the customer agility. The study presents several recommendations, including supporting the availability of the requirements for the implementation of blockchain technology to significantly and effectively support customer agility in pharmaceutical companies operating in Egypt.